Physical and mechanical properties of eastern gamagrass seed - HUANG Wencheng; ZHANG Lin; YE Dapeng; TAYLOR Alan George (浙江大学学报. 农业与生命科学版)
Conventional seed dehulling methods are unable to separate caryopses from intact cupules of eastern gamagrass as the cupules are thick and rigid, and the seeds are irregular-shaped. To put forward a feasible method of mechanical dehulling, we investigated and analysed the physical and mechanical characteristics of intact seeds, cupules and caryopses, and then evaluated the characterics that can be applied in mechanical dehulling. The testing results indicated that the tertraploid cultivar Meadowcrest had a larger seed size and a heavier seed mass than diploid Pete. The mean caryopsis mass was approximately 1/3 and 1/4 of the intact seed mass for Pete and Meadowcrest, respectively. The intact cupule was approximately twice as long as the caryopsis for all three seed lots measured. The moisture content of the cupules was significantly lower than that of the caryopses. The rupture force of the intact cupules was 1/2-2/3 of the caryopses for Pete and Meadowcrest when pressed longitudinally, respectively. Seed size, moisture content and rupture force codetermined that longitudinal seed pressing might be an effective method to remove the cupules without harming the caryopses.